Intergrated Urban Water Management : Humid Tropics - Edited by Jonathan N. Parkinson, Joel A. Goldenfum and Carlos E.M. Tucci (Boca Raton, London CRC Press Taylor & Francis Group, 2010)
Excess water in the urban environment leads to flooding, which in turn causes structural damage, risks to personal safety and disruption to city life. Water is also a major contributory factor in disease transmission as well as being the transport medium of many pollutants. These problems are of increasing concern due to climate changes and are particularly apparent in the humid tropics. This publication, the output of a project by UNESCO's International Hydrological Program on the topic, focuses on engineering aspects related to water supply, wastewater and stormwater management in the humid tropics. Flood control is dealt with, focusing on reducing vulnerability to flood disasters in urban areas. The book also addresses environmental health concerns related to the different components of the urban water system and proposes strategies for their control. It illustrates different aspects of integrated water management in the urban environment by drawing upon a set of case studies, predominantly from South America.--Publisher's description.
Include Reference and Index
Keywords: Tropics -- Urban runoff--Management -- Municipal water supply -- Water reuse -- Water-supply -- Watershed management